Illocutionary Act In The Main Character Of Weathering With You Movie - Sungkawa, Muhammad Nibroos Murtadho (Litteratura: Jurnal Bahasa dan Sastra, 2025)
This research discusses about the illocutionary act that is uttered by the main character in the Weathering with you film by using John R. Searle’s illocutionary act theory. The purposes of this research are to analyze the type of illocutionary act and functions of illocutionary act on the main character in the film. The result of the research show from the dialogue, the researcher found four types of illocutionary act in thirty nine data which are; first, ten data of representative illocutionary act indicate stating, informing, alleging, aggreging, denying, affirming, believing, and convicting. Second, ten data of directive illocutionary act indicate commanding, asking, advising, and requesting. Third, five data of commissive illocutionary act indicate offering and promising and the last, five data of expressive illocutionary act indicate thanking, praising, apologizing, appreciating, lamenting, and wishing.